The Influence of Student Management and Teacher Example on the Disciplined Character of State MTs Students in Pandeglang Regency - Suhada Suhada; Anis Zohriah; Rijal Firados (Aksara Shofa, 2024)
To determine the influence of student management and teacher example on the discipline of State MTs students in Pandeglang Regency, researchers used quantitative descriptive explanatory and inference methods. The analysis used is correlation regression. To test the hypothesis, SEM (Structural Equation Modeling) is used which is operated through the SmartPLS 4.0 program. The research results show that Student Management has a positive effect on Student Discipline as evidenced by the parameter coefficient of 0.533. with the T statistical results being greater than the T table (4.873 > 1.96) with a P value of 0.000. Likewise, the Teacher Exemplary variable has a positive effect on Student Discipline with a parameter coefficient of 0.318 with T statistical results greater than the T table (2.125>1.96) with a P value of 0.000. The results of the summary ANOVA F test or simultaneous test obtained a P value for Student Management and Teacher Exemplary which is 0.000, which is less than 0.05, which means that the independent variables, both Student Management and Teacher Exemplary, have a positive and significant effect on the Student Discipline variable simultaneously.